Autoantibodies in the pathogenesis of idiopathic inflammatory myopathies: Does the endoplasmic reticulum stress response have a role? - Corona-Sanchez, Esther Guadalupe; Martínez-García, Erika Aurora; Lujano-Benítez, Andrea Verónica; Pizano-Martinez, Oscar; Guerra-Durán, Ivette Alejandra; Chavarria-Avila, Efrain; Aguilar-Vazquez, Andrea; Martín-Márquez, Beatriz Teresita; Arellano-Arteaga, Kevin Javier; Armendariz-Borunda, Juan; Perez-Vazquez, Felipe; García-De la Torre, Ignacio; et al. (Frontiers in Immunology, 2022)
Idiopathic inflammatory myopathies (IIMs) are a group of rare, acquired autoimmune diseases characterized by profound muscle weakness and immune cell invasion into non-necrotic muscle. They are related to the presence of antibodies known as myositis-specific antibodies and myositis-associated antibodies, which are associated with various IIM phenotypes and the clinical prognosis. The possibility of the participation of other pathological mechanisms involved in the inflammatory response in IIM has been proposed. Such mechanisms include the overexpression of major histocompatibility complex class I in myofibers, which correlates with the activation of stress responses of the endoplasmic reticulum (ER). Taking into account the importance of the ER for the maintenance of homeostasis of the musculoskeletal system in the regulation of proteins, there is probably a relationship between immunological and non-immunological processes and autoimmunity, and an example of this might be IIM. We propose that ER stress and its relief mechanisms could be related to inflammatory mechanisms triggering a humoral response in IIM, suggesting that ER stress might be related to the triggering of IIMs and their auto-antibodies’ production.